Road pricing and port hinterland competitiveness: An application to the Hamburg–Le Havre range. Issue 3 (15th March 2016) - Meersman, Hilde; Sys, Christa; Van de Voorde, Eddy; Vanelslander, Thierry
ABSTRACT: Road pricing is drawing ever greater attention, not only as a means for funding infrastructure investment, but also as a way of eliminating negative externalities associated with land-based transport. The goal is to improve the environmental sustainability of such transport while maintaining its economic viability. As road transport continues to be the most prominent mode of hinterland transportation to and from seaports, road pricing may be assumed to impact on the competitiveness of those ports. This article examines the extent to which this is the case by taking a micro-research approach. It analyzes how road pricing affects the cost functions of the various actors in the logistics chain and considers the potential impact of different setups and modalities in neighboring regions and countries.